Micropattern-assisted absorption enhancement and wettability surface on ZnO via single femtosecond laser beam tailoring. (June 2022) - Li, Qisong; Shi, Haosong; Luo, Cheng; Fan, Zhengquan; Wang, Huoyu; Zhang, Long; Liu, Yi
Highlights: One-step formation of the two-dimensional surface structure on the crystalline ZnO excited via a single femtosecond laser beam. The large-area two-dimensional surface structures are achieved by a single femtosecond laser overlapped scanning. Both theory and experiments show strong absorption performance on the two-dimensional structure from the ultraviolet to near-infrared wavelengths. These micropattern structures display controlled wettability characteristic dependent on the laser energy. Abstract: Herein, we report significant micropattern-assisted absorption enhancement on crystalline ZnO fabricated by a single femtosecond laser beam (400 nm, 35 fs, kHz). This two-dimensional micropattern, which is achieved by one-step femtosecond laser tailoring, sharply contrasts the traditional laser-induced periodic surface structure. The large-area preparation of two-dimensional micropatterns can be achieved via an overlapped scanning method, showing potential practical applications. We find that the absorption shows an increasing trend, with maximum values of 90–99% in the ultraviolet spectral regions and 75–80% in the visible spectral regions. Additionally, theoretical results demonstrate that a strong electric field enhancement phenomenon exists on the two-dimensional structure from the ultraviolet to near-infrared wavelengths. We also determine the liquid contact angle of these micropattern structures, which exhibit controlled wettability characteristics that are dependent on laser energy.